Three new HLA class II alleles: DRB1*08:70, DQA1*01:13 and DQA1*03:01:03. (13th January 2016) - Balas, A.; Planelles, D.; García‐Sánchez, F.; Prior, C.; Vicario, J. L.
Summary: Three novel HLA class II alleles, DRB1*08:70, DQA1*01:13 and DQA1*03:01:03, were characterized.